Confiscations et séquestres des biens des exilés politiques dans les États italiens au xixe siècle. Questions sur une pratique et projets de recherches - Catherine Brice (Diasporas: Circulations, Migrations, Histoire)
This article is the first step in a research project aiming at a better understanding of why and how did political opponents to the Italian Restoration regimes depart in exile. Challenging the “heroic” vision of exile that has been transmitted by the actors themselves and by the “patriotic” literature of the Risorgimento and of Liberal Italy, we would like to make more explicit the conditions of departure and their motivations. This first article presents what precisely was exile, in its juridical aspects, and which links did it have with property confiscations. It turns out that the apparently obvious link between political opposition/ exile/property confiscation is far from being that obvious and that simple.